Entry, Exit, Growth, and Innovation over the Product Life Cycle - Klepper, Steven (American Economic Review, 1996)
Regularities concerning how entry, exit, market structure, and innovation vary from the birth of technologically progressive industries through maturity are summarized. A model emphasizing differences in firm innovative capabilities and the importance of firm size in appropriating the returns from innovation is developed to explain the regularities. The model also explains regularities regarding the relationship within industries between firm size and firm innovative effort, innovative productivity, cost, and profitability. It predicts that over time firms devote more effort to process innovation but the number of firms and the rate and diversity of product innovation eventually wither. Copyright 1996 by American Economic Association.